'Dark' cities: The role of interdisciplinary work in learning and supporting marginal city spaces. (July 2021) - Halligey, Alexandra
This article considers Harold Johnson's (Hariwe) 2014–2016 research project on 'Dark City', an informal vertical settlement in inner-city Johannesburg, as offering a productive arts-orientated, interdisciplinary study of and proposal for planning and design interventions in informally occupied urban spaces. Hariwe used his architectural skills to 'reverse design' the building according to its daily use by residents. Collaborators Jono Wood and Dirk Chalmers followed a similar research process with 'Dark City', using their own modalities of photography and film. The three exhibited at the Circa Gallery in Rosebank, Johannesburg in 2016, constructing an immersive simulation of the 'Dark City' environment to set their drawings, photographs and films within. This article uses the lenses of performance and performativity to argue for the research and creative processes of The 'Dark City' project as slowing down time, layering spaces across time and location and creating a sensual, immersive experience. These three effects serve to bring into view and experience the circumstances of 'Dark City', the kinds of inequalities at work in Johannesburg that produce such spaces and to propose design responses for spatial justice.